454 Barriers to initiating and implementing palliative and end of life care for children with life-limiting conditions- A mixed methods study in a UK Children's Hospital. (17th August 2022) - Umezurike, Indira; Bedford, Helen; Brierley, Joe; Dittborn, Mariana; Whitelaw, James
Abstract : Aims: To explore and discuss the barriers faced by senior paediatricians in initiating and implementing palliative and end of life care (EOLC) for children with life-limiting conditions (LLC). Specifically, the objectives were to explore barriers associated with leadership of care of the patient, communication with families, initiating and preparing advance care plans and the issues associated with dealing with other teams and professional colleagues. Methods: A mixed methods study using semi- structured interviews and an online questionnaire was carried out in a UK children's hospital that provides general and community paediatrics and multiple tertiary sub-specialities, between December 2020 and August 2021. All senior paediatricians (n=37) above registrar level were invited to take part including general paediatricians, paediatric subspecialists and associate specialists. Twelve interviews were conducted and analysed to identify themes. Questions asked were; professional experience of palliative and EOLC, leadership of care of children with LLC, communication difficulties with family and colleagues, communication issues with multidisciplinary teams and barriers to developing and implementing advance care plans. Eighteen consultant paediatricians responded to the SurveyMonkey® online questionnaire, which was a pragmatic approach to engage with paediatricians not able to be interviewed. It included questions on barriers faced in planning palliative care and who was involved in the planning process. Using a rating scale, respondents were asked to identify to what degree they agreed or disagreed with a list of barriers. ( figure 1 ) Results: Five themes emerged from the interviews: (i) problems with the leadership of end-of-life planning and care provision; (ii) problems with preparing advance care plans (ACP); (iii) lack of training in paediatric palliative care and advanced communication; (iv) problems communicating with professional teams and (v) problems communicating with families. Five barriers rated highest from the questionnaires, based on the degree to which respondents agreed or strongly agreed with listed items including; lack of training in advanced communication skills (12/18), lack of recognition of children with LLC (12/18), high profile cases (11/18), communication issues with other teams or hospitals (17/18) and family beliefs (16/18). ( figure 1 ). Duplicates and recurring themes from both studies were further analysed and the following seven themes emerged; (i) problems with the leadership of palliative planning and care provision; (ii) problems with preparing advance care plans; (iii) lack of training in paediatric palliative care and advanced communication; (iv) problems communicating with other professional teams; (v) problems communicating with families (vi) lack of recognition of children with LLC and (vii) high-profile cases. Conclusion: Barriers to effective palliative/end-of-life planning are multifaceted. Healthcare professionals must work together to establish clearer pathways to address this subject. Discussing palliative care for children with LLC at departmental meetings, peer review meetings and morbidity and mortality meetings, and advanced communication training in palliative/EOLC could help reduce these barriers.